ETHANOL MODULATES MAMMALIAN CIRCADIAN CLOCK PHASE RESETTING THROUGH EXTRASYNAPTIC GABA RECEPTOR ACTIVATION - McElroy, Brandon (2009)
Ethanol modulates the actions of multiple neurotransmitter systems, including GABA. However, its enhancing effects on GABA signaling typically are seen only at high concentrations. In contrast, although GABA is a prominent neurotransmitter in the circadian clock of the suprachiasmatic nucleus (SCN), we see ethanol modulation of clock phase resetting at low concentrations (<50 mM). A possible explanation is that ethanol enhances GABAergic signaling in the SCN through activating GABA(A) receptors that contain the δ subunit (GABA(Aδ) receptors), which are sensitive to low ethanol concentrations. Therefore, we investigated whether ethanol acts on GABA(Aδ) receptors in the SCN. Here we show that acute application of the GABA(Aδ) receptor antagonist, RO15-4513, to mouse hypothalamic slices containing the SCN prevents ethanol inhibition of nighttime glutamate-induced (photic-like) phase delays of the circadian clock. Diazepam, which enhances activity of GABA(Aγ) receptors, does not modulate these phase shifts. Moreover, we find that RO15-4513 prevents ethanol enhancement of daytime serotonergic (non-photic) phase advances of the circadian clock. Furthermore, diazepam phase-advances the SCN circadian clock when applied alone in the daytime, while ethanol has no effect by itself at that time. These data support the hypothesis that ethanol acts on GABA(Aδ) receptors in the SCN to modulate photic and non-photic circadian clock phase resetting. They also reveal distinct modulatory roles of different GABA(A) receptor subtypes in circadian clock phase regulation.